2004
DOI: 10.1007/bf02984584
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ECG-gated thallium-201 single-photon emission tomography in patients with coronary artery disease

Abstract: Assessment of post-stress left ventricular function by gated-SPECT provides incremental prognostic information and is useful in predicting cardiac events in patients with suspected or definite coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
0
23
2
Order By: Relevance
“…20 Published prognostic studies performed in the USA in patients who underwent pharmacologic stress indicate that such patients are considered at higher risk. [6][7]23 Therefore, the annualized hard event rate of 0.63% for the present study's population is as low as that of studies conducted in the USA. [4][5][6] Risk stratification is essential to the development of evidence-based strategies for improved patient care in medicine.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…20 Published prognostic studies performed in the USA in patients who underwent pharmacologic stress indicate that such patients are considered at higher risk. [6][7]23 Therefore, the annualized hard event rate of 0.63% for the present study's population is as low as that of studies conducted in the USA. [4][5][6] Risk stratification is essential to the development of evidence-based strategies for improved patient care in medicine.…”
Section: Discussioncontrasting
confidence: 56%
“…2,33 Prognostic values of left ventricular functional parameters using QGS have been demonstrated by multiple studies. [1][2][3][4][5][6][7][8][9]23,36 Previous studies found that post-stress LVEF and post-stress ESV assessed during gated SPECT had incremental predictive value in predicting cardiac death. In part, normal myocardial perfusion imaging was associated with a very low likelihood of cardiac death or myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation for known or suspected CAD using ECG-gated SPECT imaging has been established for its diagnosis and risk assessment [18][19][20]. It is a well-known fact that a comprehensive assessment of CAD requires not only morphologic information about coronary stenosis location and degree but also functional information [21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear cardiology techniques are uniquely advanced to address the determinants of prognosis by measuring stressinduced ischemia or function. These measurements include the extent of infracted myocardium and the amount of jeopardized myocardium [4].…”
Section: Introductionmentioning
confidence: 99%